PENDEKATAN EVERYDAYNESS DALAM PERANCANGAN HUNIAN PERTANIAN - Jonathan Marcelino Alexander; Nina Carina (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2021)
The food crisis is one of the issues that is currently being discussed and is predicted to occur in the future, even though Indonesia itself is an agricultural country, the food crisis cannot be avoided if it is not addressed from now on. The development and population growth of the Indonesian population, especially Jabodetabek, has made the need for food to continue to increase while the availability of land is decreasing. As a result of population growth, the need for land for housing and other activities is getting higher so that land for agriculture is increasingly displaced and away from cities. The farmer profession is also under threat due to the slow development of technology in the food sector. The future of Dwelling discusses the human lifestyle, which is affected by many factors that exist in the present. Cilincing Agro Residence is here as The Future of Dwelling and a solution to the problems of land, food, and the farmer profession itself. The lifestyle changes that have occurred in cities due to Covid-19 has shown people's interest in the process of farming. Technology helps greatly to work as a farmer so that he can now do the process of farming in the middle of the city. This project aims to bring the food supply process closer to urban areas so that it is closer to consumers, and the process is faster and more efficient. Located in the Cilincing area with the existing industrial area, warehousing, and rice fields that will develop into the Marunda economic center and residential area. This project exists as an example of modern agriculture in economic centers and settlements to achieve food security on an environmental to the urban scale. Keywords: Dwelling; Food crisis; Food security; House farming AbstrakKrisis pangan menjadi salah satu isu yang ramai dibahas saat ini dan diprediksi akan terus terjadi di masa mendatang. Walaupun Indonesia merupakan negara agraris, krisis pangan tidak dapat dihindari jika tidak ditanggapi dari sekarang. Perkembangan dan pertumbuhan populasi penduduk Indonesia khususnya Jabodetabek, membuat kebutuhan pangan terus meningkat sementara ketersediaan lahan semakin sedikit. Akibat dari pertumbuhan populasi, kebutuhan lahan untuk tempat tinggal dan aktivitas lainnya semakin tinggi sehingga lahan untuk pertanian semakin tergeser dan jauh dari kota. Profesi petani juga terancam karena lambatnya perkembangan teknologi di sektor pangan. Masa depan berhuni membahas mengenai gaya hidup manusia, yang terdampak oleh banyak faktor yang ada di masa sekarang. Cilincing Agro Residence hadir sebagai masa depan berhuni dan solusi dari masalah lahan, pangan, dan profesi petani itu sendiri. Perubahan gaya hidup yang terjadi di perkotaan akibat Covid-19 memperlihatkan ketertarikan masyarakat dalam proses bercocok tanam. Pekerjaan sebagai petani sangat terbantu dengan teknologi sehingga kini dapat melakukan proses bercocok tanam di tengah kota. Proyek ini bertujuan untuk mendekatkan proses penyediaan bahan pangan ke area perkotaan, sehingga lebih dekat kepada konsumen, prosesnya pun lebih cepat dan efisien. Berlokasi di kawasan Cilincing yang merupakan kawasan industri, pergudangan dan persawahan akan berkembang menjadi pusat ekonomi Marunda dan daerah permukiman. Proyek ini hadir sebagai contoh pertanian modern di pusat ekonomi dan permukiman untuk mencapai sekuritas pangan dalam skala lingkungan hingga kota.